The Application of the Blowfish Algorithm and the Least Significant Bit Method for Securing Student Transcripts - Iwan Ady Prabowo; wawan Laksito YS; Wahyudi Wahyudi (STMIK Sinar Nusantara, 2022)
Academic transcripts are a summary of a student's high-value achievement score and must be guaranteed in their authenticity, as well as the source from which they are issued. It was found that some universities were using technology to falsify transcripts. An example of a university in yogyakarta's special region that falsified academic transcripts. Several diplomas from makassar have been forged so that a civil servant can pass his exam, whereas in banda aceh evidence of equipment for creating fake diplomas has been found. This study seeks to prevent transcripts from being modified or falsified by locking data into student photos using blowfish and least significant bit algorithms. The purpose of this study is to keep transcripts from being easily modified or falsified. The methods of this study are data collection (student code data, gpa value, photo), encryption with blowfish, conversion of encryption results into binary form, insertion of binary values into the least significant bit method into photos, capture of encryption values from least significant bit photos, and returning messages encrypted with blowfish. In this study, the results show that this system was able to secure data and enter information into student photos with an accuracy of 100% after testing on 60 transcript value data. We can conclude that the application of blowfish and least significant bit algorithms to secure data and enter data into student photos is extremely effective in transkrip value.